THE FEMALE BODY AS THE SITE OF MEMORY AND TRAUMA: EXPLORATIONS OF GENDER, VIOLENCE AND RECONCILIATION IN CHIMAMANDA NGOZI ADICHIE’S NOVEL, PURPLE HIBISCUS - Rani S, Amala; Kumar, S. Karthik (International Journal of Research -GRANTHAALAYAH, 2025)
Women have been fighting for gender equality and fair treatment for centuries now. However, they still have a long way to go. Recent perspectives on the resilience of women show that women have been systematically taught to negate their bodily experiences to prove their mental strength. Women enduring physical abuse in most situations do not realize their victim status. This denial could lead to more trauma when women acknowledge their traumatic experience. Chimamanda Ngozi Adichie novel, Purple Hibiscus chronicles the life of an Igbo family in Nigeria. The difficult socio political environment of the country augments the personal trauma of women characters in the novel. This paper analyses the aspects of gender, trauma and violence in this novel.